WAR, INFORMATION, AND DEMOCRACY: UKRAINE’S APPROACH TO DECENTRALIZED TRANSPARENCY - Kachmarsky, Avery J. (Young Scholars Grinchenko – Seton International Journal, 2026)
This essay explores the development of decentralized, citizen-led digital transparency networks in Ukraine, from their origins in post-Soviet governance challenges to their expansion during the ongoing war with Russia. The analysis examines how open-source intelligence communities and anti-corruption platforms have strengthened democratic accountability by improving access to information, supporting independent verification, and increasing public participation. The essay also examines how these systems challenge authoritarian governance by limiting control over information and exposing misinformation. In addition, the essay considers the limitations of these networks, including issues of misinformation, ethical concerns, and long-term sustainability. This examination highlights how Ukraine’s use of digital transparency contributes to broader state-building processes while demonstrating the resilience of democratic governance during conflict.